Pengaruh Kebijakan Dividen, Ukuran Perusahaan, Dan Tingkat Suku Bunga Terhadap Harga Saham - Lathif Abdullah; Khoirunnisa Azzahra (Politeknik Raflesia Press, 2026)
This study aims to examine the effect of dividend policy, firm size, and interest rates on stock prices. This research employs a descriptive quantitative approach using secondary data obtained from companies’ annual financial statements and relevant official publications. The population of this study consists of 46 banking sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using purposive sampling, resulting in 12 companies with an observation period of five years. Panel data regression was used as the data analysis technique. Data processing and hypothesis testing were conducted using EViews 13. The results indicate that dividend policy, firm size, and interest rates simultaneously affect stock prices. Partially, dividend policy has no effect on stock prices, firm size has a positive and significant effect on stock prices, while interest rates have a negative and significant effect on stock prices.